Strengthening and Sustaining a Network of Public and Animal Health Clinical Laboratories in Pakistan: Proceedings of a Joint Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
As part of a multiyear project to promote a cooperative relationship between U.S. and Pakistani human and animal health and infectious disease experts, the Pakistan Academy of Sciences, together with the U.S. National Academies of Sciences, Engineering, and Medicine, convened a bilateral workshop in Islamabad, Pakistan, to promote best practices in and improved communications, cooperation, and coordination among public, private, military, and animal health clinical laboratories in Pakistan. The workshop, "Strengthening and Sustaining a Network of Public and Animal Health Clinical Laboratories in Pakistan," was held on September 27-29, 2016. Pakistani life science, public health, veterinary, and clinical laboratory experts, graduate students from Pakistani institutions of higher learning, and U.S. scientists/clinicians met at the workshop to explore questions facing human and animal health policy makers in Pakistan. This publication summarizes presentations and discussions of the workshop.
Keywords: Biology and Life Sciences; Conflict and Security Issues

Engaging the Private-Sector Health Care System in Building Capacity to Respond to Threats to the Public's Health and National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Disasters tend to cross political, jurisdictional, functional, and geographic boundaries. As a result, disasters often require responses from multiple levels of government and multiple organizations in the public and private sectors. This means that public and private organizations that normally operate independently must work together to mount an effective disaster response. To identify and understand approaches to aligning health care system incentives with the American public's need for a health care system that is prepared to manage acutely ill and injured patients during a disaster, public health emergency, or other mass casualty event, the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop on March 20 and 21, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Enabling Rapid and Sustainable Public Health Research During Disasters: Summary of a Joint Workshop by the Institute of Medicine and the U.S. Department of Health and Human Services - Institute of Medicine (The National Academies Press, 2015)
Over the past decade, preparedness and response capacities of government agencies, hospitals and clinics, public health agencies, and academic researchers in the United States and abroad have been challenged by a succession of public health emergencies, ranging from radiological threats to pandemics to earthquakes. Through After Action Reports, each of these emergencies has yielded important information and lessons learned that can inform future disaster response and recovery efforts. However, important information that needs to be collected during and immediately following these emergencies is often missed because of barriers and obstacles to gathering such data, such as varying institutional review board restrictions in different states, no sustainable funding network for this type of work, uncertainty on who should be involved in research response, and a lack of knowledge around how best to integrate research into response and recovery frameworks. Taking action to enable medical and public health research during disasters was the focus of a workshop held on June 12 and 13, 2014, coordinated and supported jointly by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events, National Institute of Environmental Health Sciences, the National Library of Medicine, the U.S. Department of Health and Human Services' Office of the Assistant Secretary for Preparedness and Response, and the Centers for Disease Control and Prevention. Invited speakers and participants from federal, state, and local government, academia, and community and worker organizations came together to discuss how to integrate research into existing response structures; identify critical research needs and priorities; identify obstacles and barriers to research; discuss structures and strategies needed for deployment of a research study; share ideas, innovations, and technologies to support research; and explore data collection tools and data-sharing mechanisms for both rapid and longitudinal research. Enabling Rapid and Sustainable Public Health Research During Disasters summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Examining Challenges and Possible Strategies to Strengthen U.S. Health Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
As the United States continues to adapt to a more digital, mobile, and interconnected world, health care and public health professionals have sought to better prepare for and respond to long-standing and emerging threats to the nation's health security. Health security is the collective effort to prevent, protect against, mitigate, respond to, and recover from the health consequences of natural, man-made, and technological disasters. Although substantial progress has been made in the past 15 years toward improving health care and public health systems and capacities for health security threats, many complex challenges persist, and often the nation's preparedness efforts are not sufficient.
Keywords: Health and Medicine; Conflict and Security Issues

Opportunities for the Gulf Research Program: Community Resilience and Health: Summary of a Workshop - Olsen, LeighAnne; Olson, Steve (The National Academies Press, 2015)
There are many connections between human communities and their surrounding environments that influence community resilience and health in the Gulf of Mexico. The impacts of the Deepwater Horizon oil spill on Gulf communities and ecosystems - coupled with the region's preexisting health challenges and environmental stressors - illustrate the need to better understand these connections. In the future, natural and man-made disasters, climate change impacts, and other environmental stressors will present complex challenges to the physical, mental, and social well-being of communities in the Gulf. Understanding the interrelationships among health, ecological, and economic impacts of disasters and other environmental stressors will be crucial to addressing these challenges. Opportunities for the Gulf Research Program: Community Resilience and Health summarizes a Gulf Research Program workshop held on September 22-23, 2014, in New Orleans, Louisiana. The workshop examined opportunities to improve the health, well-being, and resilience of communities in the Gulf region through discussions with about 50 participants with diverse expertise and experience. These discussions identified perceived needs, challenges, and opportunities that align with the Gulf Research Program's mission and goals - particularly its goal to improve understanding of the connections between human health and the environment to support the development of health and resilient Gulf communities. This workshop is expected to lead to the development of additional Program activities and opportunities for the research community.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

Microbial Ecology in States of Health and Disease: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Individually and collectively, resident microbes play important roles in host health and survival. Shaping and shaped by their host environments, these microorganisms form intricate communities that are in a state of dynamic equilibrium. This ecologic and dynamic view of host-microbe interactions is rapidly redefining our view of health and disease. It is now accepted that the vast majority of microbes are, for the most part, not intrinsically harmful, but rather become established as persistent, co-adapted colonists in equilibrium with their environment, providing useful goods and services to their hosts while deriving benefits from these host associations. Disruption of such alliances may have consequences for host health, and investigations in a wide variety of organisms have begun to illuminate the complex and dynamic network of interaction - across the spectrum of hosts, microbes, and environmental niches - that influence the formation, function, and stability of host-associated microbial communities. Microbial Ecology in States of Health and Disease is the summary of a workshop convened by the Institute of Medicine's Forum on Microbial Threats in March 2013 to explore the scientific and therapeutic implications of microbial ecology in states of health and disease. Participants explored host-microbe interactions in humans, animals, and plants; emerging insights into how microbes may influence the development and maintenance of states of health and disease; the effects of environmental change(s) on the formation, function, and stability of microbial communities; and research challenges and opportunities for this emerging field of inquiry.
Keywords: Health and Medicine; Conflict and Security Issues

Preparing for the Future of Disaster Health Volunteerism: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On April 26, 2017, the Forum on Medical and Public Health Preparedness for Disasters and Emergencies convened a workshop during a 4-hour session of the 2017 Preparedness Summit. Participants discussed potential characteristics of society in the year 2042 and the key resources, tools, and opportunities necessary to support the development of a robust, scalable, and regularly engaged disaster health volunteer workforce prepared for such a future. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Regional Disaster Response Coordination to Support Health Outcomes: Information Sharing and Incident Management: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
When a disaster strikes, it rarely impacts just one jurisdiction. It is important for jurisdictions to consider how they will respond to a scenario in which the entire region is impacted. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a workshop in 2014 to examine how information and incident management can augment response efforts in a complex, regional emergency. This brief summary highlights the presentation and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Regional Disaster Response Coordination to Support Health Outcomes: Surge Management: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
When a disaster strikes, it rarely impacts just one jurisdiction. It is important for jurisdictions to consider how they will respond to a scenario in which the entire region is impacted. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required to ensure effective medical and public health response to a large-scale multijurisdictional disaster. Each of the three workshops covers different topics that may strengthen regional disaster response. The third and final workshop in this series, which this document summarizes, was held in New Orleans and considered how community engagement and information sharing can impact issues of surge management across the public health and health care spectrum.
Keywords: Health and Medicine; Conflict and Security Issues

Regional Disaster Response Coordination to Support Health Outcomes: Community Planning and Engagement: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
Many catastrophic disaster plans include provisions of support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple groups and sectors together that don't routinely work with each other can augment a response to a disaster but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response.In March 2014, the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events convened a regional workshop bringing together key stakeholders to examine community planning and engagement when planning for health incidents in a large-scale response. This report highlights the presentations and discussion of that event.
Keywords: Health and Medicine; Conflict and Security Issues

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Research Priorities to Inform Public Health and Medical Practice for Ebola Virus Disease: Workshop in Brief - Institute of Medicine; National Research Council (The National Academies Press, 2014)
The 2014 epidemic of Ebola Virus Disease (EVD), caused by a filovirus, has affected multiple countries in West Africa (Guinea, Liberia, Sierra Leone, Nigeria, and Senegal), along with Spain and the United States, becoming the worst EVD outbreak since its discovery in 1976. Until 2014, previous outbreaks have been confined to smaller geographic areas and often only affected a few hundred people. Confirmed and suspected cases of EVD have now occurred in the United States through human-to-human transmission, requiring the U.S. medical and public health systems to prepare for and respond to domestic cases of EVD. The heightened awareness and attention to the disease in the United States has also led to questions from affected communities on specific characteristics of the virus, how the virus behaves, and personal protective equipment and personal protective behaviors that can be used to prevent its spread and reduce exposure. At the request of the Office of the Assistant Secretary for Preparedness and Response, the National Institutes of Health, and the Centers for Disease Control and Prevention, the Institute of Medicine , in collaboration with the National Research Council, convened a workshop on November 3, 2014, with key stakeholders and experts to discuss the research priorities that could guide medical and public health practice. Discussions included the degree of transmission and biopersistence of the virus under a range of conditions and on a variety of materials, as well as issues of handling potentially infected materials, decontamination, and the training and personal protective equipment usage of traditional and nontraditional workers involved in the full spectrum of this response. Research Priorities to Inform Public Health and Medical Practice for Ebola Virus Disease summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Preparing for a Rapid Response to Major Marine Oil Spills: Protecting and Assessing the Health and Well-Being of Communities: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On August 2–3, 2017, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Preparing for a Rapid Response to Major Offshore Oil Spills: A Workshop on Research Needs to Protect the Health and Well-Being of Communities. Its objectives were to explore research needs and other opportunities for improving public health preparedness, response, and protection related to oil spills; consider how to work within and how to complement the existing oil spill response framework to improve the protection of community health and well-being; to inform discussions about how the Gulf Research Program and other divisions of the National Academies can support these efforts; and to foster connections among public health, oil spill practitioners, disaster research communities, and leaders from communities affected by oil spills. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Nationwide Response Issues After an Improvised Nuclear Device Attack: Medical and Public Health Considerations for Neighboring Jurisdictions: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Our nation faces the distinct possibility of a catastrophic terrorist attack using an improvised nuclear device (IND), according to international and U.S. intelligence. Detonation of an IND in a major U.S. city would result in tens of thousands to hundreds of thousands of victims and would overwhelm public health, emergency response, and health care systems, not to mention creating unprecedented social and economic challenges. While preparing for an IND may seem futile at first glance, thousands of lives can be saved by informed planning and decision making prior to and following an attack. In 2009, the Institute of Medicine published the proceedings of a workshop assessing the health and medical preparedness for responding to an IND detonation. Since that time, multiple federal and other publications have added layers of detail to this conceptual framework, resulting in a significant body of literature and guidance. However, there has been only limited planning effort at the local level as much of the federal guidance has not been translated into action for states, cities and counties. According to an informal survey of community preparedness by the National Association of City and County Health Officials (NACCHO), planning for a radiation incident ranked lowest in priority among other hazards by 2,800 local health departments. The focus of Nationwide Response Issues After an Improvised Nuclear Device Attack: Medical and Public Health Considerations for Neighboring Jurisdictions: Workshop Summary is on key response requirements faced by public health and health care systems in response to an IND detonation, especially those planning needs of outlying state and local jurisdictions from the detonation site. The specific meeting objectives were as follows: - Understand the differences between types of radiation incidents and implications of an IND attack on outlying communities. -Highlight current planning efforts at the federal, state, and local level as well as challenges to the implementation of operational plans. -Examine gaps in planning efforts and possible challenges and solutions. -Identify considerations for public health reception centers: how public health and health care interface with functions and staffing and how radiological assessments and triage be handled. -Discuss the possibilities and benefits of integration of disaster transport systems. -Explore roles of regional health care coalitions in coordination of health care response.
Keywords: Health and Medicine; Conflict and Security Issues

Technologies to Enable Autonomous Detection for BioWatch: Ensuring Timely and Accurate Information for Public Health Officials: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
The BioWatch program, funded and overseen by the Department of Homeland Security (DHS), has three main elements—sampling, analysis, and response—each coordinated by different agencies. The Environmental Protection Agency maintains the sampling component, the sensors that collect airborne particles. The Centers for Disease Control and Prevention coordinates analysis and laboratory testing of the samples, though testing is actually carried out in state and local public health laboratories. Local jurisdictions are responsible for the public health response to positive findings. The Federal Bureau of Investigation is designated as the lead agency for the law enforcement response if a bioterrorism event is detected. In 2003 DHS deployed the first generation of BioWatch air samplers. The current version of this technology, referred to as Generation 2.0, requires daily manual collection and testing of air filters from each monitor. DHS has also considered newer automated technologies (Generation 2.5 and Generation 3.0) which have the potential to produce results more quickly, at a lower cost, and for a greater number of threat agents. Technologies to Enable Autonomous Detection for BioWatch is the summary of a workshop hosted jointly by the Institute of Medicine and the National Research Council in June 2013 to explore alternative cost-effective systems that would meet the requirements for a BioWatch Generation 3.0 autonomous detection system, or autonomous detector, for aerosolized agents . The workshop discussions and presentations focused on examination of the use of four classes of technologies—nucleic acid signatures, protein signatures, genomic sequencing, and mass spectrometry—that could reach Technology Readiness Level (TRL) 6-plus in which the technology has been validated and is ready to be tested in a relevant environment over three different tiers of temporal timeframes: those technologies that could be TRL 6-plus ready as part of an integrated system by 2016, those that are likely to be ready in the period 2016 to 2020, and those are not likely to be ready until after 2020. Technologies to Enable Autonomous Detection for BioWatch discusses the history of the BioWatch program, the role of public health officials and laboratorians in the interpretation of BioWatch data and the information that is needed from a system for effective decision making, and the current state of the art of four families of technology for the BioWatch program. This report explores how the technologies discussed might be strategically combined or deployed to optimize their contributions to an effective environmental detection capability.
Keywords: Health and Medicine; Conflict and Security Issues

Dispensing Medical Countermeasures for Public Health Emergencies: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
On March 3-4, 2008, the Institute of Medicine (IOM) Forum on Medical and Public Health Preparedness for Catastrophic Events hosted a workshop titled "Medical Countermeasures Dispensing." The overall objective was to discuss a range of solutions to rapidly provide medical countermeasures to protect large numbers of people prior to or during a public health emergency, such as a bioterrorist attack or infectious disease outbreak. The United States is currently unprepared to confront the range of threats it is facing, such as an intentional anthrax release, severe acute respiratory syndrome (SARS), or pandemic influenza, and it must plan aggressively to counteract the threat of these and other future public health emergencies. Countermeasure dispensing must harness all types of imaginative partnerships between public and private institutions, working together in ways tailored to meet individual community needs. This workshop summary highlights the presentations and subsequent discussion that occurred at the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Public Health Risks of Disasters: Communication, Infrastructure, and Preparedness: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2005)
The National Research Council's Disasters Roundtable and the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine were established as mechanisms for bringing various stakeholders together to discuss timely issues in a neutral setting. The goal was not to resolve these issues, but to create an environment conducive to scientific debate. The members of the respective Roundtables comprise representatives from academia, industry, nongovernmental agencies, and government, whose perspectives range widely and represent the diverse viewpoints of researchers, federal officials, and public interest. This report is the summary of a workshop was convened by the two Roundtables as a contribution to the debate on the health risks of disasters and the related need to build capacity to deal with them. The meeting was strengthened by integrating perspectives from these two fields, so that the agenda represented information from both communities and provided an opportunity to look at some of the most pressing research and preparedness needs for health risks of disasters.
Keywords: Earth Sciences; Health and Medicine; Conflict and Security Issues

The Public Health Emergency Medical Countermeasures Enterprise: Innovative Strategies to Enhance Products from Discovery Through Approval: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
During public health emergencies such as pandemic influenza outbreaks or terrorist attacks, effective vaccines, drugs, diagnostics, and other medical countermeasures are essential to protecting national security and the public's well-being. The Public Health Emergency Medical Countermeasures Enterprise (PHEMCE)—a partnership among federal, state, and local governments; industry; and academia—is at the forefront of the effort to develop and manufacture these countermeasures. However, despite the PHEMCE's many successes, there are still serious challenges to overcome. Government-funded medical research is not always focused on countermeasures for the most serious potential threats, and it is difficult to engage pharmaceutical and biotechnology companies to develop and manufacture medical countermeasures that have a limited commercial market.
Keywords: Health and Medicine; Conflict and Security Issues

Vector-Borne Diseases: Understanding the Environmental, Human Health, and Ecological Connections: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Vector-borne infectious diseases, such as malaria, dengue fever, yellow fever, and plague, cause a significant fraction of the global infectious disease burden; indeed, nearly half of the world's population is infected with at least one type of vector-borne pathogen (CIESIN, 2007; WHO, 2004a). Vector-borne plant and animal diseases, including several newly recognized pathogens, reduce agricultural productivity and disrupt ecosystems throughout the world. These diseases profoundly restrict socioeconomic status and development in countries with the highest rates of infection, many of which are located in the tropics and subtropics.
Keywords: Health and Medicine; Conflict and Security Issues

Public Health Systems and Emerging Infections: Assessing the Capabilities of the Public and Private Sectors: Workshop Summary - Institute of Medicine (The National Academies Press, 2000)
The Forum on Emerging Infections was created in 1996 in response to a request from the Centers for Disease Control and Prevention and the National Institutes of Health. The goal of the forum is to provide structured opportunities for representatives from academia, industry, professional and interest groups, and government to examine and discuss scientific and policy issues that relate to research, prevention, detection, and management of emerging infectious diseases. A critical part of this mission has been the convening of a series of workshops. Public Health Systems and Emerging Infections summarizes the fourth in a series of five workshops. With a focus on our knowledge and understanding of the role of private and public health sectors in emerging infectious disease surveillance and response, the participants explored the effects of privatization of public health laboratories and the modernization of public health care. The issues discussed included epidemiological investigation, surveillance, communication, coordination, resource allocations, and economic support.
Keywords: Health and Medicine; Conflict and Security Issues